f(x)=x^6-73x^4-657x^2+729

let x^2=A

f(x)=a^3-73a^2-657a+729

from observation, a=1 is a root

therefore

x^2=1

x= +/- 1

on further analysis, x=9 and x=3i also satisfy the equation.

Using the Conjugate theorem,

x=-3i is also a root of the equation. So is x=-9

Hence using the above Values,

the factored polynomial is

(x−1)(x+1)(x−9)(x+9)(x+3i)(x-3i)

that is

(x−1)(x+1)(x−9)(x+9)(x^2+9)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up